Monotasking: Solusi Distraksi Era Modern - Sarla Nabila; Ira Qurrotul Ain; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
Abstract - The aim of this study is to find out the benefits and tips for implementing monotasking in everyday life. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from the Greatmind YouTube channel entitled "On Marissa's Mind: Monotasking" presented by him. The results of this study explain that we often encounter many people in big cities who have a lot of work that they have to complete in just one day, so many people force themselves to become multitaskers, namely doing 2 or even 3 jobs at once. At the same time, the focus becomes fragmented and the work cannot be completed optimally and the mind even becomes explosive. The research began with a small number of people who thought that being a multitasker would speed up all the work they had. Introducing monotasking can change a person's perspective on carrying out their work. So that all the work they have can be completed one by one and the results obtained will be maximum.